The application of DFT in catalysis and adsorption reaction system. (October 2018) - Weijing, Ding; Weihong, Zhou; Xiaodong, Zhang; Baofeng, Zhao; Lei, Chen; Laizhi, Sun; Shuangxia, Yang; Haibin, Guan; Guanyi, Chen; Liang, Zhu; Ge, Song
Abstract: Density function theory (DFT) can be used to investigate the mechanisms of complex catalysis and adsorption reactions. On this basis, the application of DFT in catalysis/adsorption reaction system is summarized in this paper. Then it puts forward ideas for research, explores the DFT simulation of CO2 adsorption and tar removal in biomass thermal conversion and eventually lays a foundation for experimental and theoretical exploration.